Analysis of Factors Affecting Operator Performance with Partial Least Square Approach - Tommy Ivantoro; Bambang Syairudin (Institut Teknologi Sepuluh Nopember, 2020)
UP PT is unable to meet the targets set in the SdOF, SOF, and PS categories. There are several things that cause it, such as High Pressure Heater leakage, and boiler pipes leakage. Coal switching which also have an impact on the frequent occurrence of derating and human error. This condition is defined by operator incompetence, there is an increase in the number of late for work in 2018. Study conducted to improve operator performance. The questionnaire was used as a medium for data collection of the entire population at UP PT since analyzed with the Partial Least Square method. The results shows compensation variables, organizational culture, training effectiveness had a significant influence on employee performance with and without mediated by work motivation. Therefore, the company carries out performance improvement related to compensation through dispensation arrangements, leave, improvement of supporting facilities. It organize operational safety standards for workforce formation, conducting work instructions review for the organizational culture. The allocation of bussiness trip and basic maintenance for training effectiveness. Then work motivation by setting talent criteria that consider to the preparation of outstanding candidates.